An optical cloak made of dielectrics - Valentine, Jason; Li, Jensen; Zentgraf, Thomas; Bartal, Guy; Zhang, Xiang (Nature Materials)

Self-Organisation and Self-Optimization - Meyer auf der Heide, Friedhelm; Rammig, Franz-Josef (Public Service Review: Science and Technology)

Language and Logic in German Post-Hegelian Philosophy - Peckhaus, Volker (The Baltic International Yearbook of Cognition, Logic and Communication, Bd. 4: 200 Years of Analytical Philosophy)

Guest-editor des Focus On "Corpus Linguistics - Methods and Approaches" - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus-based and corpus-driven approaches: An investigation of the verb do - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus Linguistics: a discipline on the move - Mindt, Ilka (Anglistik. International Journal of English Studies)

Algorithmische und komplexitätstheoretische Aspekte kombinatorischer Preisoptimierung (Computational Aspects of Combinatorial Pricing Problems) - Briest, Patrick (it - Information Technology)

Die Welterbeliste - zwischen Kanonbildung und Kanonverschiebung - Seng, Eva- Maria
Demnächst in: ZS ejournal Kunstgeschichte, LMU München. Open Peer Reviewed Journal www.kunstgeschichte-ejournal.net

Arno Eugen Fritsche - Seng, Eva- Maria (Protestantische Profile im Ruhrgebiet. 500 Lebensbilder aus 5 Jahrhunderten)

Denkmalpflege und kulturelles Erbe - Seng, Eva- Maria (MUT. Forum für Kultur, Politik und Geschichte)

Elias Holl - Seng, Eva- Maria (Killy-Literaturlexikon (Neuauftritt), München, Berlin)

„Aufgabe, Wirken, Möglichkeiten: 150 Jahre Kirche und Kunst in Württemberg“ - Seng, Eva- Maria (Blätter für württembergische Kirchengeschichte)

Laudatio auf Dr. Reinhard Höppner - Seng, Eva- Maria (Ehrenpromotion Höppner (Paderborner Universitätsreden 113))

Gemeinsam lernen: Der Masterstudiengang „Kulturerbe/Studies in Cultural Heritage“ - Seng, Eva- Maria (Deutsche Hochschulen im Dialog mit der arabischen Welt,)

„Phantasie oder Vernunft: Ästhetische und architektonische Visionen von Städten und Gärten“ - Seng, Eva- Maria (Ist eine andere Welt möglich? Utopische Zwischenrufe. Multidisziplinäre Analysen und Reflexionen des utopischen Denkens)

Hoffmann von Fallersleben. Internationales Symposion Corvey/Höxter 2008

Neulektüren – New Readings

Foreword - D. Kleinberg, Robert; Scheideler, Christian (Theory Comput. Syst.)

Towards a Scalable and Robust DHT - Awerbuch, Baruch; Scheideler, Christian (Theory Comput. Syst.)

Robust random number generation for peer-to-peer systems - Awerbuch, Baruch; Scheideler, Christian (Theor. Comput. Sci.)